2020
DOI: 10.1038/s41598-020-71643-1
|View full text |Cite
|
Sign up to set email alerts
|

SMOC2, an intestinal stem cell marker, is an independent prognostic marker associated with better survival in colorectal cancers

Abstract: We aimed to investigate the expression profile of SPARC-related modular calcium-binding protein 2 (SMOC2) during colorectal cancer (CRC) progression and assess its prognostic impact in CRC patients. In our study, we showed that SMOC2 transcript level was higher in CRC samples than in normal mucosa (P = 0.017); this level was not associated with candidate cancer stem cell markers (CD44, CD166, CD133, and CD24) or intestinal stem cell markers (LGR5, ASCL2, and EPHB2) except for OLFM4 (P = 0.04). Immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…A volcano plot for strongly up/downregulated genes in the iHUCO stem cell sub-population consistently showed suppression of Lgr5-expressing cells (Supplementary Fig. 5d ) whereas genes such as SMOC2 78 , which promotes matrix assembly and cell adhesiveness, were overexpressed. Our in situ hybridization for Lgr5 confirmed that this stem cell marker was suppressed in iHUCOs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 91%
“…A volcano plot for strongly up/downregulated genes in the iHUCO stem cell sub-population consistently showed suppression of Lgr5-expressing cells (Supplementary Fig. 5d ) whereas genes such as SMOC2 78 , which promotes matrix assembly and cell adhesiveness, were overexpressed. Our in situ hybridization for Lgr5 confirmed that this stem cell marker was suppressed in iHUCOs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Higher expression of TEADs, as well as association with poor patient survival, have been observed in many cancers including CRC [52,53]. On the other hand, the target gene SMOC2 was recently shown to be a favorable prognostic biomarker for better clinical outcomes in a large cohort of CRC patients [54]. Therefore, the MethReg prediction that transcription factor TEAD3 suppresses target gene SMOC2 is consistent with the oncogenic role of TEAD3 and the favorable prognostic potential of SMOC2.…”
Section: Simulation Analysismentioning
confidence: 56%
“…The correlation between SMOC2 and diseases has been widely reported. Jang et al[34] reported that SMOC2 is a tumor suppressor in colorectal cancer and can elevate the expression of SMOC2 and suppress cell migration, colony and sphere formation. However, Lu et al[35] reported on the suppression function in colon carcinoma invasion and migration of ARNTL2 via decreased SMOC2-EMT activity.…”
Section: Discussionmentioning
confidence: 99%